Effect of long-term aging treatment on the structure and oxidation resistance of Cr coatings under high-temperature steam. (March 2023) - Xiang, Yang; Zhao, Sha; Liu, Chunhai; Yang, Hongyan; Zhang, Wei; Wang, Hui; Zhang, Ruiqian; He, Hengji; Liu, Sujuan
Abstract: Cr coatings were deposited on Zr-4 tubes by arc ion plating to explore the effect of different aging treatment times at low temperature on the steam oxidation performance of Cr coatings. The intrinsic relationship between the coating grain evolution and oxidation behavior after different aging times was analyzed by EBSD. The mid-term aging treatment improve the oxidation resistance of the Cr coating. After long-term aging treatment, a significant amount of Cr2 O3 in the grain boundaries close to the Zr-4 substrate preferentially reacts with Zr, which is the reason for the serious degradation of the performance of the Cr coating. Highlights: The normal operating temperature environment of the reactor is simulated by low temperature and long-term aging treatment. The intrinsic relationship between the coating grain evolution and oxidation behavior after different aging times was analyzed. The reduction in grain boundary density of the Cr coating improves the oxidation resistance. The performance degradation of Cr coating is attributed to the preferentially reaction of Cr2 O3 with Zr.